Otimização dos parâmetros para obtenção de nanotubos em Ti-Cp por anodização eletroquímica e aplicação na liga experimental Ti-35Nb-7Zr - Rosa, Jorge Luiz [UNESP] (2013)
This study has as its main objective the optimization of the process of obtaining nanotubes self-assembled on the Ti-Cp flat surface by electrochemical anodization technique and application of this experimental condition on the surfaces of the Ti-35Nb-7Zr experimental alloy and commercial Ti implant. In the optimization study of main factors of the process (electrolyte, anodization time and potential) was used the method Design of Experiments - DOE. The formation of the layer of titania was observed by Field Emission Gun Scanning Electron Microscopy (FEG-SEM) and Energy dispersive X-ray spectroscopy (EDS). The heat treatment used to stabilize the crystalline phase of the oxides conducted at 300, 400 and 500°C revealed the formation of anatase from 400oC, but above this temperature occurs closing and coalescence of the nanotubes. Electrochemical tests performed in Ringer's solution showed that titanium surfaces coated with TiO2 nanotubes are less corrosion resistant than titanium as received. By employing the DOE was possible to verify that the best experimental setting condition in obtaining self-organized nanotubes for Ti-Cp was the glicerol-H2O/NH4F electrolyte, and controlling the factors, potential, anodization time and concentration of NH4F, was obtained the oxide with the desired characteristics. The potential was the factor that most influenced the process. The application of the best experimental condition on commercial Ti implant enabled the formation of nanotubes with small change in morphology. But on the Ti-35Nb-7Zr alloy surface were observed significant changes in nanotubes morphology and different dimensions from that observed for Ti-Cp